Production Thematic Maps of Bearing Capacity of Shallow Foundation for Al-Basrah Soil Using Standard Penetration Data and GIS - Majeed Sabaa; Alaa Salman; Ammar Dakhil; Saba Jawad; Mahdi Karkush; Ahmed Athab (Journal of Rehabilitation in Civil Engineering)
The Geographic Information System (GIS) is one of the modern database software which is used to collect, analyze, display, processing and produce geographic information maps for a specific objective. In addition, a statistical analysis can be generated within GIS on specific data to produce quantitative results. In this study, the GIS utilized to produce thematic maps showing the variation of bearing capacity of shallow foundation in Al-Basrah province soil. All the features mentioned above illustrate the importance of GIS exploring more valuable results such as the bearing capacity of shallow foundation from the results of standard penetration tests (SPT) conducted in Al-Basrah province soil. The total number of boreholes drilled was 135 distributed irregularly in the study area. In each borehole, three SPTs were performed at depths of 1.5, 6, and 9.5 m measured from the existing ground level (EGL). The results of the study can be summarized by the production of thematic maps showing the variation of the bearing capacity of the soil over the whole area of Al-Basrah city correlated with several depths. These maps can be used by different local authorities to predict soil bearing capacity and choose a suitable type of foundation. In addition, it can be utilized to assess the foundations of existing and irregularly constructed buildings and to assess the extent of the risks of failure and collapse.